Intra‐annual variability and environmental controls over transpiration in a 58‐year‐old even‐aged stand of invasive woody Juniperus virginiana L. in the Nebraska Sandhills, USA. Issue 5 (4th July 2012) - Awada, Tala; El‐Hage, Rita; Geha, Makram; Wedin, David A.; Huddle, Julie A.; Zhou, Xinhua; Msanne, Joseph; Sudmeyer, Robert A.; Martin, Derrel L.; Brandle, James R.
ABSTRACT We investigated the intra‐annual variability and environmental controls over transpiration (E) in a planted, even‐aged (58 years; 537 trees ha−1), experimental forest of invasive native Juniperus virginiana in the Nebraska Sandhills, with three canopy classes (dominant, co‐dominant, and suppressed) by using sap flux techniques, in a year where drought was absent (2008, 34% above average precipitation). Daily E was closely linked to growing‐season length and variability in the environment. Minimum and average daily air temperatures, photosynthetically active radiation, and precipitation explained the majority of the intra‐annual daily variability in E. Vapour pressure deficit was a significant factor in spring and summer, shallow volumetric soil water content (VSWC 0·2 m) was important during summer particularly June, and deep VSWC (0·6 m) was a significant factor in January and August. E was highest in the dominant trees and contributed to the majority ( 77%) of stand transpiration (Ec) on site because of their larger canopy size, greater tree density, more leaf area, and accessibility to water resources compared with the co‐dominant and suppressed tree canopies, which contributed to 16% and 7%, respectively. Ec averaged 413 mm year−1, corresponding to 24% of potential evapotranspiration. Soils were significantly drier in the J. virginiana stand than in adjacent C4‐dominated grasslands, which could be due to the longer growing season over which physiological activity extends in J. virginiana compared with C4‐dominated grasslands in the region and precipitation interception by the canopy and forest floor, which evaporates before reaching the soil. Copyright © 2012 John Wiley & Sons, Ltd.